Applying Design Science Research to develop a Technique to Evaluate the Usability and User eXperience of Learning Management Systems - Nakamura, Walter T.; Oliveira, Elaine H. T. de; Conte, Tayana (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2018: Anais do XXIX Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2018.953, 2018)
As Internet-based technology becomes more accessible, learning institutions have been adopting platforms such as Learning Management Systems (LMSs) to support and also complement face to face learning. Their widespread adoption raises the importance to evaluate them regarding quality in use attributes such as usability and User eXperience (UX). This paper presents the application of Design Science Research (DSR) to develop a technique and a tool to evaluate the usability and UX of LMSs called TUXEL. By applying DSR, we ensure a high level of rigor in the development process, combining theory and practice. The empirical studies indicated that TUXEL is adequate, in addition to providing better results compared to other techniques.